Circle of Willis variants are not associated with thrombectomy outcomes. Issue 2 (12th October 2020) - Seifert-Held, Thomas; Eberhard, Katharina; Christensen, Soren; Hofer, Edith; Enzinger, Christian; Albers, Gregory W; Lansberg, Maarten
Abstract : Background: The circle of Willis (COW) is part of the brain collateral system. The absence of COW segments may affect functional outcome in patients with ischaemic stroke undergoing endovascular therapy. Methods: In 182 patients in the Diffusion and Perfusion Imaging Evaluation for Understanding Stroke Evolution 2 Study and the CT Perfusion to Predict Response to Recanalisation in Ischaemic Stroke Project, COW anatomy was evaluated on postinterventional magnetic resonance angiography. The absence of the posterior communicating artery or the first segments of posterior or anterior cerebral arteries ipsilateral to the ischaemic infarction was rated as an incomplete COW. Logistic regression was applied to evaluate an association with the patients' modified Rankin scale (mRS) at 90 days after stroke Results: An incomplete ipsilateral COW was not predictive of the patients' mRS at 90 days after stroke. Significant associations were shown for the patients' baseline National Institutes of Health Stroke Scale (NIHSS), age and reperfusion status. The effect size suggests that a significant association of an incomplete COW with the mRS at 90 days may be obtained in cohorts of more than 3000 patients. Conclusions: Compared with the established predictors NIHSS, age and reperfusion status, an incomplete COW is not associated with functional outcome after endovascular therapy.